Colorectal Origin: A Marker of Favorable Outcome in Krukenberg Tumor? Results from Clinical and Prognostic Analysis - Thakur, Purnima; Sharma, Mukesh; Chauhan, Ashish; Pal, Kapil M.; Thakur, Shabnam; Gupta, Manish; Kaushal, Shilpa (South Asian Journal of Cancer, 2024)
This study aimed to identify the prognostic factors affecting the survival of patients suffering from Krukenberg tumor (KT) and also to determine the survival in these patients. A retrospective review of patients diagnosed with KT between January 2015 and December 2021 was conducted at a tertiary cancer center. Clinicopathological variables were scrutinized, and survival analysis was performed. Thirty-six patients were enrolled in this study. The median age at diagnosis was 48 years (ranging from 22 to 71 years). The median overall survival (OS) was 9.9 months (95% confidence interval [CI]: 6.6 to 13 months). The mean OS for tumors originating in the colorectal region was longer compared to that for tumors of other sites (15.4 vs. 9 months, respectively; p = 0.048). In univariate analysis, patients who received chemotherapy had better survival, while those presenting with ascites had a poor prognosis. No correlation was observed between age, menstrual status, bilaterality, size of ovarian metastases, extent of metastatic disease, metastasectomy, and survival. Multivariate Cox regression analysis showed that chemotherapy predicted a favorable survival outcome (hazard ratio [HR] = 0.200, 95% CI: 0.046–0.877, p-value = 0.033). KT is an aggressive tumor with a median OS of less than a year. Chemotherapy may improve survival. Patients with a primary tumor in the colorectal region have a better outcome, while those presenting with ascites indicate a poor prognosis.
Keywords: Krukenberg tumor; prognostic factors; survival; chemotherapy